Synaptic Pruning by Microglia: Lessons from Genetic Studies in Mice - de Deus, Junia Lara; Faborode, Oluwaseun Samuel; Nandi, Sayan (Developmental neuroscience, 2024)
Neural circuits are subjected to refinement throughout life. The dynamic addition and elimination (pruning) of synapses are necessary for maturation of neural circuits and synaptic plasticity. Due to their phagocytic nature, microglia have been considered as the primary mediators of synaptic pruning. Synaptic pruning can strengthen an active synapse by removing excess weaker synapses during development. Inappropriate synaptic pruning can often influence a disease outcome or an injury response. This review offers a focused discussion on microglial roles in synaptic pruning, based on the evidence gathered from genetic manipulations in mice. Genetically labeled microglia and synapses often allow assessment of their interactions in real time. Further manipulations involving synaptically localized molecules, neuronally or glial-derived diffusible factors, and their respective cognate receptors in microglia provide critical evidence in support of a direct role of microglia in synaptic pruning. We discuss microglial contact-dependent "eat-me," "don't-eat-me," and "find-me" signals, as well as recently identified noncontact pruning, under the contexts of neural circuit, brain region, developmental window, and an injury or a disease state.